External Time Monitoring in Time‐Based Prospective Memory: An Integrative Framework. Issue 12 (14th December 2022) - Munaretto, Giulio; Stragà, Marta; Mäntylä, Timo; Mioni, Giovanna; Missier, Fabio Del
Abstract: We propose a new integrative framework of external time monitoring in prospective memory (PM) tasks and its relation with performance. Starting from existing empirical regularities and our theoretical analysis, the framework predicts that external monitoring in PM tasks comprises a first stage of loose monitoring to keep track of the passage of time, and a subsequent stage of finer‐grained monitoring, based on interval reduction, to meet the PM deadline. Following our framework, we predicted and observed in three different datasets ( N = 375): (1) a marked increase in external monitoring frequency in the final part of the period of the PM task, well captured by a proportional rate exponential growth function; (2) a positive association between individual compliance with this monitoring pattern and PM performance; (3) a positive relation between monitoring frequency in the time window immediately preceding the PM deadline and PM performance at the individual level; and (4) good individual compliance with an interval reduction pattern in external monitoring, especially in the time window closer to the PM deadline. These results support the proposed integrative framework, which has the potential to foster future research on external monitoring in PM and in other fields of cognitive science.